Türkei und Menschenrechte: Sonderweg am Bosporus - Reinke, Sarah; Karaboya, Haydar; Bar-Abraham, Abdulmesih; Stocker, Franziska (Pogrom, 2004)
Zülch, Tilman; Reinke, Sarah; Karaboya, Haydar: Menschenrechte in der Türkei: Sonderweg am Bosporus. - S. 14-16